2020
DOI: 10.1002/wsb.1085
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Methods for Detecting Island Spotted Skunks

Abstract: Island spotted skunks (Spilogale gracilis amphiala) are endemic to 2 of the California Channel Islands (CA, USA)-Santa Cruz and Santa Rosa. The status of skunks is uncertain, although incidental captures in traps set for island foxes (Urocyon littoralis) suggest that skunks have declined to low numbers. We superimposed wildlife cameras at fox traps in 2016 and 2017 to provide a second measure of skunk detectability. On both islands, detection rates of skunks with fox traps (0.92/100 operating nights) and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…At the county level, the detection rates in Coryell (0.36%) and Waller (0.27%) compared favorably with those in Missouri and the rate in Harris County (0.73%) was comparable with 0.81% reported for Arkansas (Hackett et al 2007). Recent assessment of the detectability of the island spotted skunk (S. g. amphiala) resulted in low detection rates for both live traps (0.92%) and camera traps (0.72%; Bolas et al 2020). We confirmed that live traps, track plates, and cameras traps likely would detect plains spotted skunks if the species is present, although in areas with low abundance, such as the FWNCR, multiple surveys may be required for detection.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…At the county level, the detection rates in Coryell (0.36%) and Waller (0.27%) compared favorably with those in Missouri and the rate in Harris County (0.73%) was comparable with 0.81% reported for Arkansas (Hackett et al 2007). Recent assessment of the detectability of the island spotted skunk (S. g. amphiala) resulted in low detection rates for both live traps (0.92%) and camera traps (0.72%; Bolas et al 2020). We confirmed that live traps, track plates, and cameras traps likely would detect plains spotted skunks if the species is present, although in areas with low abundance, such as the FWNCR, multiple surveys may be required for detection.…”
Section: Discussionmentioning
confidence: 87%
“…Recent assessment of the detectability of the island spotted skunk ( S. g. amphiala ) resulted in low detection rates for both live traps (0.92%) and camera traps (0.72%; Bolas et al. 2020). We confirmed that live traps, track plates, and cameras traps likely would detect plains spotted skunks if the species is present, although in areas with low abundance, such as the FWNCR, multiple surveys may be required for detection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations